KONSUMSI BBM PREMIUM DI INDONESIA DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Arya W Darmaputera; Dendy Kurnaedy (Bina Ekonomi, 1999)
This study examines the factors that & determine 'premium' petroleum demand in Indonesia, focusing on the period  of 1980-1995. Employing a logarithmic  model this study also measures price-elasticity, income-elasticity, and the cross-elasticity of premium petrol with lubricants. It is found that the demand is inelastic towards income, inelastic towards price, and that lubricants arc strong complementariness for premium petrol.  Thus it can be concluded that premium petrol is a normal good (neither superior nor inferior), a relatively basic need with little or no substitutes and its demand is complementary with the demand or lubricants. Since premium petrol is  a basic need for Indonesian people  Government  with almost no substitutes, the should not take rash steps that would cause the price of petrol  apparent that if Indonesia would like to re4uce the consumption of premium petrol, price policies would not be very effective as price-elasticity is low. Non-price policies, eg., introduction of  alternative energy, would probably be more potent.